Efecto de las diferentes concentraciones de NaCl en la germinación y crecimiento de plántulas de Phaseolus lunatus L. “pallar bebe” en condiciones de laboratorio - VASQUEZ SERIN, Juana (2019)
In the present research work, the objective was to determine the effect of sodium chloride on the germination and growth of seedlings of Phaseolus lunatus L. "pallar bebe"; using a completely randomized experimental design with 5 treatments with concentrations of 200, 400, 600, 800 and 1000 mg NaCl / ml and a control with 3 repetitions. Previously, 540 seeds were selected, which were disinfected in 1% sodium hypochlorite "bleach" for 2 minutes; then 30 seeds were distributed per repetition, a total of 90 for each treatment in a technopor container with paper towels moistened according to the treatments, then they were placed in a dark chamber at 20.5 ° C ± 1.03 ° C to germinate until seedlings days. The results of the Analysis of Variance and the Tukey test at 95% confidence show significant differences in the parameters of germination and growth; in the germination 100% is obtained for the different treatments with a higher average germination rate in T5 with 6.6 days and the lowest in the control with 1.1 days, the highest germination speed in the control is 7.5 and the lowest at T5 is 0.6, the lowest germination index is for T4 and T5 which indicates toxicity and the highest 80% in the control. In the seedlings the average length of the hypocotyl and the lowest radicle was given in T5 and the highest in the control, the index of tolerance of the seedlings as the index of vigor to NaCl, higher was observed in the T1 and the lower in T5.